A General Catalyst Based on Cobalt Core–Shell Nanoparticles for the Hydrogenation of N‐Heteroarenes Including Pyridines - Murugesan, Kathiravan (Angew Chem Int Ed Engl, 2020)
Herein, we report the synthesis of specific silica‐supported Co/Co(3)O(4) core–shell based nanoparticles prepared by template synthesis of cobalt‐pyromellitic acid on silica and subsequent pyrolysis. The optimal catalyst material allows for general and selective hydrogenation of pyridines, quinolines, and other heteroarenes including acridine, phenanthroline, naphthyridine, quinoxaline, imidazo[1,2‐a]pyridine, and indole under comparably mild reaction conditions. In addition, recycling of these Co nanoparticles and their ability for dehydrogenation catalysis are showcased.